Validity of Flipbook-Based Practicum Guide Fungus Identification as A Learning Solution In The Covid-19 Pandemic - Mahfudotin, Siti; Cintamulya, Imas (Bioedukasi: Jurnal Pendidikan Biologi, 2021)
The period of the pandemic COVID-19 has affected educational activities in Indonesia so that the learning process that was previously carried out offline must be transferred to offline or online. This makes new changes for teachers by utilizing digital media or technology as alternative media in conveying information as e-learning learning. The practicum that was previously carried out offline must change to online by being carried out at their respective homes. The practicum continues but must be accompanied by a guideline as an organizer of the practicum. Thus the practical instructions are designed in a digital book to make it easier for students to access them via the internet. Based on this, a study was conducted to develop a practical guide flipbook on the validity of a learning solution during the COVID-19 pandemic. The development model used is 4-D (four D). The model only arrives at three stages because of the current conditions, namely the COVID-19 pandemic which includes the definition, design, and development stages. The technique of collecting data is by distributing instruments in the form of validation sheets to expert validators. The validator consists of 2 Biology teachers, 1 linguist, and 1 student. The validation sheet consists of five validity aspects, namely material/content aspects, presentation aspects, language aspects, graphic aspects, and evaluation. The results of the validation test are then averaged to find out the validity. Based on the results of the validation test, the average value was 81.5%. This value is categorized as very valid